Effects of Self-Compassion and Self-Disclosure on Mental Health through Spirituality: A Study on Adolescents in Orphanages - Akbar Nur Aziz; Azam Syukur Rahmatullah; Akif Khilmiyah (Islamic Guidance and Counseling Journal, 2023)
Some adolescents who live in orphanages may feel a lack of affection from their parents during their development; So, some orphanage adolescents experience a lack of guidance in dealing with problems in life, including mental health problems. To prevent this, it is necessary to have an attitude of self-compassion and self-disclosure of adolescents to their foster parents. In addition, it is necessary to strengthen the spirituality of orphanage adolescents to prevent adolescents from mental health disorders. This study aims to find a match and habit of the model of the influence of self-compassion and self-disclosure through spirituality on the mental health of orphanage adolescents. This research uses a survey method with a quantitative descriptive approach to correlational models. The study subjects were orphanages as many as 165 samples were taken randomly at 3 orphans in Yogyakarta. Research data were obtained from observations, interviews, and research questionnaires. Analyze the research data using SmartPLS version 3 software with a two-stage embedded second-order approach. The results of this study show that a match of the research model was found between structural results and empirical data. This study implies that strengthening mental health for adolescents living in foster care can be done by consistently instilling the value of spirituality and improving self-compassion attitudes.